THE CURRENT STATE OF KOREAN LANGUAGE EDUCATION AND KOREAN TEACHER TRAINING COURSES IN KAZAKHSTAN AND GRADUATES’ EMPLOYMENT STRATEGIES (Focusing on the case of Al-Farabi Kazakh National University) - Lee, Byong Jo (Journal of Oriental Studies, 2022)
Korean Studies in Kazakhstan received scholarships or support and benefits to study in Korea and were able to make great progress in a short period of time. Of course, the role and contribution of the Kazakhstan government, which opened the way for Korean Studies education at universities, legally and institutionally through education policy, is also absolutely important. However, despite this series of achievements, Korean Studies have been receiving great attention and love from many Kazakhstanians, but the current legal status of Korean in elementary, middle and high schools does not extend to the second foreign language. Therefore, based on the development of Korean Studies for nearly 30 years, I have now developed a plan so that graduates who especially majored in “korean language” can work in elementary, middle, and high schools using their majors rather than simply in commercial workplaces. As an alternative, first, through continuous contact at the government level, efforts are made to adopt Korean as a second language, and based on this, a pedagogical curriculum and appropriate experts are recruited. In addition, the Korean government should provide support for graduates and teachers em- ployed in the program, even for a certain period of time, and establish a system for joint management of the program between Korean Education Center in Almaty and the Department of the Far East(Korean Studies). Key words: Korean Studies, Korean Language, Al-Farabi Kazakh National University, Department of the Far East(Korean Studies), Korean Education Center in Almaty.